Antibacterial efficacy of Satureja montana L. essential oil encapsulated in methyl-β-cyclodextrin/soy soluble polysaccharide hydrogel and its assessment as meat preservative. (December 2021) - Cui, Haiying; Wang, Yiwei; Li, Changzhu; Chen, Xiaochen; Lin, Lin
Abstract: As an emerging packaging material, hydrogels have been attracting attention to inhibit foodborne pathogens by encapsulating antimicrobial substances. Herein, an antibacterial packaging material was prepared via incorporation of methyl-β-cyclodextrin/ Satureja montana L. essential oil inclusion complexes (MCD/SEO-ICs) into soy soluble polysaccharide (MCD/SEO-SSPS) hydrogel. During, the addition of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) facilitated the formation of amido linkage between -NH2 and –COOH. Compared with SSPS hydrogel, the MCD/SEO-SSPS hydrogel exhibited a more compact structure. What's more, physical characterization indicated that combining MCD/SEO-ICs with SSPS could improve the hardness, adhesiveness and springiness of hydrogel. More importantly, a good antibacterial activity of SPSS hydrogel was obtained with the addition of MCD/SEO-ICs. On this basis, the application test demonstrated that the prepared MCD/SEO-SSPS hydrogel could reduce the visible count of Staphylococcus aureus ( S. aureus ) in meat samples by 3.5 Log CFU/g during 7-days storage, which retained the freshness of chilled pork and extended the shelf life. The above results indicated that MCD/SEO-SSPS hydrogel can be used as a safe and effective active packaging material for chilled meat preservation. Graphical abstract: Image 1 Highlights: Satureja montana L. essential oil (SEO) have a good inhibitory effect on S. aureus. Methyl-β-cyclodextrin inclusion complex (MCD-IC) improved the solubility and stability of SEO. MCD-IC enhanced the mechanical strength and release characteristics of the hydrogel. MCD/SEO-soy soluble polysaccharide hydrogels can be used as antibacterial packaging material.